Penerapan Teknik Dampening Pada Vibraphone Dalam Lagu - David Friedman (Saraswati)
Dampening performance technique contained in the “Mirror from Another”song by David Friedman has degree of difficulty that is not so complicated. Itrequired only a high knowledge in applying of the dampening technique beautifully inthis song. The author analyze application of dampening technique so that it canprovide new insights in playing the vibraphone. This song has the characteristic ofthe tones that are not have a lot of variety and a relaxed tempo. This study aims tofind the application of dampening performance technique.Key words : Dampening, Vibraphone, Mirror From Another